Mosques, Prayer Rooms, Islamic Boarding Schools and Madrasahs as Centers for Community Empowerment and Preservation of Islamic Culture - Muhammad Fadli Satrianu; Didik Himmawan; Amaliyah (Konsultan Jurnal Ilmiah Indonesia, 2025)
The purpose of this study is to explore government and community efforts in overcoming the challenges of intolerance, radicalism, and terrorism in Indonesia. Mosques, prayer rooms, Islamic boarding schools, and madrasahs have a strategic role in shaping the character of society and preserving Islamic culture. This study aims to examine the role of these four institutions as centers for community empowerment and cultural preservation in historical and contemporary contexts. Using library research methods, this study analyzes classical and modern literature to explore the relevance of their roles. The findings reveal that mosques and prayer rooms not only function as places of worship but also as centers for education, moral development, and social activities. Islamic boarding schools play an important role in preserving Islamic traditions through the teaching of classical Islamic texts (kitab kuning) and promoting an Islamic way of life, while also acting as agents of social change by supporting the economic empowerment of the community. Madrasahs, through the integration of religious and general curricula, foster a generation that is academically competitive and has character in the global era. The four institutions complement each other in strengthening Islamic values ​​and fostering a harmonious, independent, and competitive society. This study highlights the importance of collaboration between these religious institutions and elements of society to maintain their relevance amidst modernization and globalization. By optimizing the role of mosques, prayer rooms, Islamic boarding schools, and madrasahs, Islamic culture can continue to be preserved as an integral part of community life now and in the future.